A Contrastive Analysis of Diglossia in Japanese and Javanese - Br Barus, Murniati; Nurhidayati, Siti Ayu; Pujiono, Mhd.; Gustianingsih (International Journal Linguistics of Sumatra and Malay, 2024)
This study aims to describe the linguistic situation of the use of Japanese and Javanese varieties in a diglossic situation. This research uses descriptive qualitative method by using data analysis method of pairing method. The method used in data collection is the listening method embodied in the tapping technique and when necessary the researcher uses the listening technique with the recording technique. The results showed that the findings in Japanese in jougei kankei (seniority relationship) determine the type of language used in communication. Language levels include the variety of ordinary forms (Futsu) in informal conversations and polite forms (Teinei) respectful forms (Keigo) in formal conversations. The finding of Javanese language that the situation of diglossia between speakers of Javanese speech community in Asahan dominantly occurs in familiar symmetrical and familiar asymmetrical situations. In the familiar symmetrical situation, all language varieties used are ngoko lugu variant forms. The relationship of social factors that are parallel and the relationship of familiar closeness between speakers causes the use of ngoko varieties with the variant form of ngoko lugu between speakers, while in familiar asymmetrical situations it is dominated by using the form of ngoko lugu, the rest are variant forms of ngoko alus and ngoko alus-ngoko lugu and lugu krama varieties.